Soviet-type economies and reform failures - A touch of the socialist midas - Jan Winiecki (Intereconomics, 1987)
Various market-type reforms have been introduced into the economies of Eastern Europe in recent years. These have often been warmly applauded in the West, but their success so far has been at best marginal. Without radical changes in the fundamentals of the Soviet-type economic system such reforms can have no lasting impact.
Keywords: 330